Author Correction: Recursive patterns in online echo chambers - Brugnoli, Emanuele; Cinelli, Matteo; Quattrociocchi, Walter; Scala, Antonio (Scientific reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.